ANALYSIS OF VICTIMOLOGY WHICH CAUSES VICTIMS IN DEMONSTRATIONS (Pekanbaru Omnibuslaw Demonstration Case Study, 2020) - Tasya Sofiatul Afrida Nasution; M Zulherawan (Sisi Lain Realita, 2023)
The student demonstration that took place in front of the Riau Province DPRD building in 2020 was a form of approval for the omnibuslaw issue. Demonstrations that occur often end in violence or anarchy. There are two factors that cause problems in the study discussed, namely internl factors and external factors. The research method used is an exploratory qualitative research method. The author finds that a demonstration is a forn of movement intiated by a group of people with the aim of conveying aspirations. However, in reality on the ground, demonstrations always result in victims and the victims of course already know the risks if the demonstration ends in chaos. In this case, the government should also be more alret in responding to circulating issues so that multiple actions do not occur. Students should also be able to control their emotions and remain focused on demands.